The enzyme activities of pancreas and small intestinal contents in the Malaysian village chicken and broiler strains - Kadhim, Khalid Kamil; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Babjee, Shaik Mohamed Amin; Saad, Mohd Zamri (Universiti Putra Malaysia Press, 2014)
The digestive enzyme activities of the pancreas and small intestinal contents were examined in two strains of chickens which differ in growth rates from 1 day to 4 months of age. The total body weight (BW) of Commercial Broiler Chicken (CBC) showed marked increase (P<.05) during the experiment, in contrast to Malaysian village chicken (MVC) which only increased slowly over the same period. The pancreas weight of MVC (g/100g BW) was greater (P<.05) than CBC throughout the experiment except for 1 day of age. The pancreatic enzyme activity (unit/g and unit/100g BW) was significantly higher (P<.05) in the CBC, particularly at 10 days old. However, there was no difference between the strains at 20 to 56 days of age for amylase and 120 days for chymotrypsin. The enzyme activity (unit/g) for all intestinal segments increased with age in both strains. In particular, CBC attained a maximal value at 10 days of age for jejunal and ileal trypsin, as well as for duodenal, jejunal and ileal chymotrypsin. Meanwhile, the enzyme activities (unit/100g BW) decreased with age for both the strains. In specific, CBC had a relatively greater enzyme activities (P<.05) at day 1, except for the jejunal trypsin and the chymotrypsin. Thereafter, the relative activities were higher for MVC until the end of the experiment. Although significant differences in the digestive enzyme activities were obtained between the two strains, these differences were generally associated with the differences in body weight. The selection affected the development rate of the synthesis of these enzymes according to the body requirements and biological function and this might affect the digestion and finally the growth rate.